Performance of Phosphazene-Containing Polymer-Strengthened Concrete after Exposure to High Temperatures - Tanyildizi, Harun; Asilturk, Erol (Asce-Amer Soc Civil Engineers, 2018)
The strength properties of concrete strengthened with a polymer including phosphazene after exposure to high temperatures is investigated in this study. The Taguchi L-25 (5(5)) method was used to reduce the number of experiments and to find the parameters affecting the experimental results. Percentage of phosphazene in the monomer (0%, 1%, 2%, 3%, and 4%), curing period (28, 60, 90, 180, and 365 days), cement content (300, 350, 400, 450, and 500kg/m(3)), and high temperature (20 degrees C, 200 degrees C, 400 degrees C, 600 degrees C, and 800 degrees C) were chosen as experimental parameters. For the experiments, 100x100x100mm cubes were prepared. The specimens were removed from water after the end of predetermined curing times and dried at 105 +/- 5 degrees C. Then, they were exposed to temperatures of 200 degrees C, 400 degrees C, 600 degrees C, and 800 degrees C. The next step was impregnation of the samples with a vinyl acetate monomer containing phosphazene for a 24-h period under atmospheric conditions. The polymerization of specimens was conducted at 60 degrees C for 4h. The compressive strength, ultrasonic pulse velocity, and changes in weight were determined for the specimens. Furthermore, X-ray powder diffraction (XRD), energy dispersive X-ray (EDX), and scanning electron microscope (SEM) image analyses of specimens were carried out. The findings showed that the best results were found from specimens with low cement content and 3% polymer containing phosphazene. Therefore, this study has found that polymer containing phosphazene can strengthen buildings exposed to high temperatures. (C) 2018 American Society of Civil Engineers.
Keywords: Concrete; Phosphazene; Polymer; High temperature; Strength properties